The Impact of Quantum leadership on Promoting Change through the Perceived Communication Quality of Change and the Possibility of Change - Abbas Ghaedamini Harouni; Reza Ebrahimzadeh Dastjerdi; homera aebdi; Mehrdad Sadeghi de cheshmeh (Allameh Tabataba'i University Press, 2018)
The purpose of this study was to investigate the effect of quantum leadership on changes in quality through perceived communication quality and changeability. The present research was applied in terms of purpose and in terms of collecting descriptive information of correlation type. The statistical population of this study was all of the staff employed in the Islamic Azad University of Sefahan in Sefahan to be 1,000. Using the Cochran sampling formula, 287 individuals were selected through simple random sampling method. The research tool was Shleton Quantum Leadership Standards Questionnaire (2003) and questionnaire. The standard of commitment to change was Fedour et al. (2009) and perceived standard communication questionnaire of change proposed by Miller and Mang (1985) and the Readiness Change Standard questionnaire provided by Holt et al. (2007). On the other hand, Cronbach's alpha method was used to quantify the quantum leadership questionnaire (93/0) and The Change Commitment Questionnaire (0.81) and Perceived Communication from Change (0.85) and Readiness for Change (0.92) questionnaire were estimated. Data analysis was carried out at the inferential level including structural equation modeling. The results of the research showed that quantum leadership through its readiness for change has a positive and significant impact on the commitment to change, which has a coefficient of 0.39, but does not have a significant effect through the quality of the relationship on commitment to change. Also, the direct impact on the commitment to change is also Not meaningful.